Regulation of the nitrate uptake process in grass species - Serezino, Luís Henrique Damasceno (2020)
Due to the negative environmental and economic consequences of excessive and indiscriminate use of N fertilizer, there is an increasing need for developing more efficient crops for N uptake. As nitrate is the main inorganic N source available in most soils, there has been a notable research effort to understand the nitrate uptake process, a key factor in the improvement of Nitrogen Use Efficiency (NUE), and the molecular factors that modulate it. Thus, the knowledge acquired in model plants about the molecular factors and regulatory mechanisms of genes encoding Nitrate Transporters (NRTs) responsible for nitrate uptake could be used to improve NUE in crops. The improvement of NUE is a challenge to allow environmentally friendly agriculture to support the growth of the human population and the consequent food demand, since the intensive use of N fertilizers threat both crop sustainability and food security. The physiological and molecular characterization of the nitrate acquisition process in Brachypodium distachyon, a grass model plant, could help to improve non-model crops with higher biological complexity such as sugarcane. 15N-ammonium and 15N-nitrate influx analyses in B. distachyon upon N-replete and N-deficient conditions revealed that ammonium is the preferential inorganic N source. A negative feedback regulation of nitrate uptake process by ammonium in Brachypodium plants under N provision and N resupply was observed. BdNRT2.1and BdNRT2.2 expression analyses suggest that both proteins are the main B. distachyon NRT2 transporters responsible for nitrate acquisition. Both identified BdNRT3 members were co-expressed with BdNRT2.1 and BdNRT2.2. So, the 15N-nitrate influx analysis and transcript accumulation of members of the two-component complex (NRT2/ NRT3) after ammonium chloride provision and ammonium nitrate resupply treatments suggest the transcriptional regulation of HATS in B. distachyon. Conversely, studies with sorghum and sugarcane revealed distinct regulation of HATS nitrate uptake process under nitrate resupply. 15N-nitrate influx assays showed high nitrate uptake by sorghum \'BTX623\' cultivar and the sugarcane \'IAC87-3396\' genotype. Expression analysis of genes encoding NRT2 and NRT3, HATS complex components, exhibit distinct transcriptional regulation among sugarcane genotypes. The lack of correlation between the accumulation of NRT2.1 and NRT3.1 proteins with the 15N-nitrate influx suggest the presence of a mechanism controlling nitrate transport in sorghum and sugarcane roots at post-translational level. This putative allosteric regulation of the HATS complex would be the major player on nitrate uptake in roots of sorghum and sugarcane. A better understanding of the mechanisms and molecules involved in the post-translational regulation of the nitrate uptake process and, therefore, in the signaling pathway of this N source in grasses would bring about the development of crops with higher NUE.